(untitled) - Sommerville, Kerry L. (Hoboken, N.J., 2008)
It has been prepared to help you effectively use the text in classroom presentation and for discussion, review and exammination. To this end, the following materials have been included for each chapter: Active learning tips for Tales from the fiel,...
Keywords: Hospitality industry,Công nghiệp khách sạn; Personnel management,Quản trị nhân sự